2008
DOI: 10.1210/er.2007-0026
|View full text |Cite
|
Sign up to set email alerts
|

Syndromes of Ketosis-Prone Diabetes Mellitus

Abstract: Ketosis-prone diabetes (KPD) is a widespread, emerging, heterogeneous syndrome characterized by patients who present with diabetic ketoacidosis or unprovoked ketosis but do not necessarily have the typical phenotype of autoimmune type 1 diabetes. Multiple, severe forms of beta-cell dysfunction appear to underlie the pathophysiology of KPD. Until recently, the syndrome has lacked an accurate, clinically relevant and etiologically useful classification scheme. We have utilized a large, longitudinally followed, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 51 publications
4
140
0
8
Order By: Relevance
“…De t e r mi n a n t s o f 2 8 -d a y Ca s e -f a t a l i t y a mo n g Di a b e t i c P a t i e n t s wi t h a S e c o n d a r y Di a g n os (3,22). Additionally, in the study of Ko et al (4) (24). In Taiwan, Yan et al (2000) (25) …”
Section: And Southern Taiwan (17%) (5) Also In the Recent Calendar Ymentioning
confidence: 95%
“…De t e r mi n a n t s o f 2 8 -d a y Ca s e -f a t a l i t y a mo n g Di a b e t i c P a t i e n t s wi t h a S e c o n d a r y Di a g n os (3,22). Additionally, in the study of Ko et al (4) (24). In Taiwan, Yan et al (2000) (25) …”
Section: And Southern Taiwan (17%) (5) Also In the Recent Calendar Ymentioning
confidence: 95%
“…However, it has been suggested that there is a subgroup of type 2 diabetes characterized by acute onset diabetic ketosis, and subsequent normoglycemic remission without insulin therapy [1]. Ketosis-prone type 2 diabetes (KPD) belongs to this subgroup, which has mainly been reported in AfricanAmericans [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, autoimmunity has been detected in a subset of patients with type 2 diabetes, which has led to a revision of the classification to include LADA, latent autoimmune diabetes of adulthood, underscoring the continuum between type 1 and type 2 diabetes, and raising questions as to the role of immunity and inflammation in ␤-cell dysfunction and death in type 2 diabetes (Syed et al 2002; Pozzilli and Buzzetti 2007). Conversely, forms of ketosis prone diabetes due to severe ␤-cell dysfunction but without evidence of autoimmunity are now recognized (Balasubramanyam et al 2008). Decreased ␤-cell function also underlies early-onset monogenic forms of diabetes termed MODY (maturity-onset diabetes of the young) resulting from mutations in transcription factors that regulate ␤-cell development and differentiation.…”
mentioning
confidence: 99%